2018
DOI: 10.1159/000492592
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunosuppressive Treatment May Improve Short-Term Renal Outcomes in Chinese Patients with Advanced IgA Nephropathy

Abstract: Background/Aims: Treatment of advanced Immunoglobulin A nephropathy (IgAN) patients with estimated glomerular filtration rate (eGFR) below 45 mL/min per 1.73 m2 remains inconsistent. The aim of this study is to compare the effects of corticosteroid and immunosuppressant therapies among these patients. Methods: A total of 201 adult patients with advanced IgAN (eGFR < 45 mL/min/1.73 m2 and proteinuria > 1 g/24h at biopsy) grouped into supportive care (SC), steroids alone (CS), and steroids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
3
14
0
1
Order By: Relevance
“…In the current cohort, we found that more patients in C2 group received immunosuppressant than patients in C1 and C0 groups. Moreover, aggressive treatment contain immunosuppressant could effectively improve the renal outcome of IgAN patients (especially patients with crescents), which is similar to several other studies [12, 13]. Inconsistent with previous reports [10], C1 did not independently predict renal outcome in our cohort, and treatment responses were similar in patients in C1 and C0 groups.…”
Section: Discussionsupporting
confidence: 89%
“…In the current cohort, we found that more patients in C2 group received immunosuppressant than patients in C1 and C0 groups. Moreover, aggressive treatment contain immunosuppressant could effectively improve the renal outcome of IgAN patients (especially patients with crescents), which is similar to several other studies [12, 13]. Inconsistent with previous reports [10], C1 did not independently predict renal outcome in our cohort, and treatment responses were similar in patients in C1 and C0 groups.…”
Section: Discussionsupporting
confidence: 89%
“…In the Cox multivariate analysis, it was found that hypertension, Scr level, endocapillary hypercellularity, and tubular atrophy/interstitial fibrosis were significant independent predictors of poor renal outcome. These results are similar to previous reports (12,16). Although several reports (17) have shown that patients with cellular or fibrocellular crescents have worse prognoses, crescents were not found to be associated with renal survival in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the use of immunosuppressant drugs for IgAN is in dispute due to the difficulty in balancing between toxicity and long-term renal survival (11). Some reports found that immunosuppressants might lower proteinuria and improve renal outcome in patients with IgAN (12,13), while several studies did not find prominent benefits from an immunosuppressive combination protocol (14,15). Our study indicated that renal survival was significantly better in the CS group than in the IT group during the follow-up period.…”
Section: Discussionmentioning
confidence: 56%
“…Notably, in the STOP-IgAN cohort, 1 out of 55 patients in the steroid monotherapy group and 5 out of 54 patients in supportive care group progressed to ESRD, demonstrating a slight trend for steroids being superior to supportive care, although there was no statistical significance, which might have resulted from the relatively small number of patients. Moreover, some retrospective studies have reported that immunosuppression is effective for treating IgAN 34,35 . Therefore, we believe that the addition of steroids to supportive care is beneficial to patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%